2008
DOI: 10.1029/2008gl034433
|View full text |Cite
|
Sign up to set email alerts
|

Short‐period solar cycle signals in the ionosphere observed by FORMOSAT‐3/COSMIC

Abstract: We analyze 2 years of the FORMOSAT‐3/COSMIC GPS radio occultation data to study the response of the Earth's ionosphere to the solar rotation (27‐day) induced solar flux variations. Here we report electron density variations in the ionosphere (∼100–500 km) associated with the 27‐day solar cycle. The peak‐to‐peak variation in electron density at low latitudes in the F2 region is about ∼104–105 electrons cm−3 or 20–40%, and can be as high as 60% depending on altitude, latitude, and season. The half and double per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Periodograms of TEC at different individual sites were performed, but no strong 58.4 day peaks were found. A double of the 27 day solar rotation cycle giving a 54 day period in electron density was previously found [ Liang et al , 2008], but the 58.4 day peak is well defined. However, 58.4 days is approximately one sixth of the GPS orbital repeat period (∼351.4 days [ Ray et al , 2008]).…”
Section: Resultsmentioning
confidence: 83%
“…Periodograms of TEC at different individual sites were performed, but no strong 58.4 day peaks were found. A double of the 27 day solar rotation cycle giving a 54 day period in electron density was previously found [ Liang et al , 2008], but the 58.4 day peak is well defined. However, 58.4 days is approximately one sixth of the GPS orbital repeat period (∼351.4 days [ Ray et al , 2008]).…”
Section: Resultsmentioning
confidence: 83%
“…There is also usually a *27 day periodicity associated with solar rotation (see e.g. Liang et al 2008;Hocke 2008;Min et al 2009), together with seasonal variations in the activity of the ionosphere at different latitudes and heights (e.g. Liu et al 2009).…”
Section: Characteristics and Variabilitymentioning
confidence: 99%
“…Our results are consistent with other studies. For instance, Liang et al [2008] analyzed ionospheric electron density profiles retrieved from FORMOSAT‐3/COSMOC radio occultation observations and found that at 2.5°N and 355 km the ∼27 day signal of electron density had a peak‐to‐peak variation of about 10%–25%, corresponding to a NSD of ∼3.5%–8.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we focus on the morphology and mechanisms of the ∼27 day variation of N m F 2 . There have been many studies of N m F 2 variations with this periodicity [e.g., Bartels , 1950; Titheridge , 1973; Kane et al , 1995; Forbes et al , 2000; Rishbeth and Mendillo , 2001; Pancheva et al , 2002; Rich et al , 2003; Prabhakaran Nayar et al , 2004; Wang et al , 2007; Oinats et al , 2008; Astafyeva et al , 2008; Afraimovich et al , 2008; Liang et al , 2008; Hocke , 2008; Min et al , 2009; Borries and Hoffmann , 2010]. However, the latitudinal, seasonal, local time, and solar cycle changes of this variation are not fully understood.…”
Section: Introductionmentioning
confidence: 99%